Ni-Mo bimetallic oxides/rGO nanocomposites as counter electrode for the application of DSSCs - Visnupriya S.; Prabavathi N.; Vijayakumar P. (Elsevier B.V., 2025)
The one-pot chemical reduction process was used to generate the bimetallic Ni?Mo nanoparticles attached to reduced graphene oxide (rGO) nanocomposite, which was then used as an effective counter electrode in dye-sensitized solar cells (DSSC). Diffraction patterns were used to investigate the face-centered crystalline structure of the spherical-shaped Ni?Mo nanoparticles that were uniformly anchored over the surface of rGO. The nanoparticles had an average diameter ranging from 70 to 120 nm. Raman spectroscopy was utilized to investigate the structural interaction that was created by the presence of bimetallic nanoparticles and the graphene oxide support. In addition, the rGO/Ni?Mo counter electrode equipped DSSC demonstrated the highest solar to electrical energy conversion efficiency of 3.11% under irradiation from one sun with a fill factor (FF) of 0.48. ? 2024